Comparative evaluation of the efficacy of two anesthetic gels (2% lignocaine and 20% benzocaine) in reducing pain during administration of local anesthesia - A randomized controlled trial - Manisha Nair; Deepa Gurunathan (Wolters Kluwer Medknow Publications, 2019)
Background and Aims: Topical anesthetic agents are widely used in the field of pediatric dentistry to reduce pain and apprehension during administration of local anesthesia. Various topical anesthetic agents are available, among which the most commonly used ones are lignocaine and benzocaine. Hence we planned this study to compare and evaluate the effectiveness of topical anesthesia on needle insertion pain during administration of inferior alveolar nerve block. Material and Methods: This double blind clinical study included 30 children of 4-8 years of age who were divided equally into two groups: Group A-2% lignocaine hydrochloride gel (Lox 2%) and Group B-20% benzocaine gel (ProGel-B). The intervention involved assessment of pain perception by the child during administration of inferior alveolar nerve block. The child's pain assessment was done using modified Wong-Baker pain rating scale. The ratings were subjected to statistical analysis. Results: In Group A, 6.7% (N = 1) showed slight pain, 66.7% (N = 10) showed moderate pain, and 26.7% (N = 4) showed severe pain. In Group B, 46.7% (N = 7) showed no pain, 46% (N = 7) showed slight pain, and 6.7% (N = 1) showed moderate pain on needle insertion. (P value -0.000). Conclusion: This study demonstrates that there is a highly significant difference between the topical anesthetic effectiveness of 2% lignocaine and 20% benzocaine on needle insertion pain in inferior alveolar nerve block. Twenty percent benzocaine showed better results than 2% lignocaine in reducing the needle insertion pain.